2012
DOI: 10.7763/ijbbb.2012.v2.89
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methyl Jasmonate and Salicylic Acid on Alkaloid Production from in vitro Culture of Stemona sp.

Abstract: Abstract-Plant tissue culture technique combined with elicitors is required to produce plant secondary metabolites. The results showed that both elicitors (methyl jasmonate and salicylic acid) could enhance the production of Stemona alkaloids in the Stemona sp. culture. Among these elicitors, salicylic acid was found to be the most effective elicitor. The plantlet which was elicited with 100 µM salicylic acid for 1 week showed an increase of 1′,2′-didehydrostemo-foline and stemofoline production at 1.69 fold a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…This all causes the induction of ROS bursting. This whole process is lead to the production of secondary metabolites [42] Silybum marianun hairy root culture are able to generate all flavonolignans that are found in the part of fruit but also found in the seeds and leave, while in dried fruit the production was generally lower [34,[43][44][45][46][47] This study is in agreement with our results as in our study fresh extract was used to check on HPLC that showed production of flavonolignans in leaves of the S. marianum plant [48][49][50][51][52][53].…”
Section: Standardsupporting
confidence: 85%
“…This all causes the induction of ROS bursting. This whole process is lead to the production of secondary metabolites [42] Silybum marianun hairy root culture are able to generate all flavonolignans that are found in the part of fruit but also found in the seeds and leave, while in dried fruit the production was generally lower [34,[43][44][45][46][47] This study is in agreement with our results as in our study fresh extract was used to check on HPLC that showed production of flavonolignans in leaves of the S. marianum plant [48][49][50][51][52][53].…”
Section: Standardsupporting
confidence: 85%
“…The similar study showed that production of stemofoline alkaloids enhanced 1.42fold in root extracts of Stemona sp. treated with 1.0 MeJa, when compared with control plants [31]. MeJa treatment induced the accumulation of dihydrosanguinarine alkaloid about 1.5-fold higher than in control [32].…”
Section: Influences Of Meja and Put On Tryptanthrin And Indirubin Productionmentioning
confidence: 83%
“…The insignificant increased effect of SA on the biomass obtained in our results confirm those of Kang et al (2004) in the adventitious roots of Scopolia parviflora. Chaichana et al (2012) reported that, in general, SA elicitation has a negative effect on growth. In an earlier study, it was reported that SA treatment slightly inhibited the growth of Salvia miltiorrhiza cell cultures (Li et al, 2003).…”
Section: Discussionmentioning
confidence: 99%